2020
DOI: 10.34172/jlms.2020.41
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antibacterial Effects of Photodynamic Therapy and an Irrigation Activation System on Root Canals Infected With Enterococcus faecalis: An In Vitro Study

Abstract: Introduction: Enterococcus faecalis is a resistant bacterium which is the most abundant species in infected root canals. Photodynamic therapy (PDT) is a method for killing the bacteria with active Oxygen radicals generated in a photosensitizer when exposed to centralized light. Furthermore, as a new method of canal disinfection, a variety of irrigation activation systems have been introduced, one of which is GentleFile (GF) with rotary movements and spiral effects for antibacterial action. This study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…infections in root canals; several authors have indicated that it is an ineffective disinfectant when used alone. However, as a complementary treatment, it significantly improves the classic chemomechanical treatment, eliminating the bacterial load in most studies [ 40 , 59 , 71 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…infections in root canals; several authors have indicated that it is an ineffective disinfectant when used alone. However, as a complementary treatment, it significantly improves the classic chemomechanical treatment, eliminating the bacterial load in most studies [ 40 , 59 , 71 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, PDT was performed at 650 nm and 200 mW for 60 sec, which was significantly better than nanoneem against E. faecalis. The same parameters were used by Asnaashari M., who reported an 80% decrease in the bacteria inside the canal compared to NaOCI [51].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that aPDT makes significant bacterial elimination possible, even in cases with antibiotic-resistant species. Several in-vitro studies have confirmed the positive effect of adding aPDT to conventional irrigation methods (sodium hypochlorite or chlorhexidine) on Enterococcus faecalis reduction (Ghorbanzadeh et al, 2018;Asnaashari et al, 2020). There is also promising evidence of the lethal effect of aPDT on Enterococcus faecalis in both primary endodontic treatments and re-treatments (Tennert et al, 2014).…”
Section: Applications Of Antimicrobial Photodynamic Therapy In Endodo...mentioning
confidence: 95%